Extraordinary magnetic field effects mediated by spin-pair interaction and electron mobility in thermally activated delayed fluorescence-based OLEDs with quantum-well structure. Issue 8 (8th February 2019) - Pan, Ruiheng; Tang, Xiantong; Hu, Yeqian; Zhu, Hongqiang; Deng, Jinqiu; Xiong, Zuhong
Abstract : We fabricated quantum-well organic light-emitting diodes (QW-OLEDs) based on thermally activated delayed fluorescence (TADF) and measured their magnetic field effects curves over various magnetic field ranges. Abstract : We fabricated quantum-well organic light-emitting diodes (QW-OLEDs) based on thermally activated delayed fluorescence (TADF) and measured their magneto-electroluminescence (MEL) and magneto-conductance (MC) curves over various magnetic field ranges. When the number ( N ) of QWs was 7, the MC curves showed a flat structure within the magnetic field range 5 < | B | < 20 mT. The flat structure vanished with the use of a higher electron mobility material, which we attribute to competition between the dissociation of triplet excitons by holes and scattering of electrons by triplet excitons in the QW-TADF-OLEDs. In addition, when N ranged from 3 to 9, the MEL curves in the range | B | < 10 mT presented a W-like line-shape and the MC curves in the range | B | < 10 mT showed variation of their line-shape from W-like to negative Lorentzian-type; however, the B -dependent efficiency Mη ( i.e., MEL–MC) curves in the range | B | < 10 mT, which were independent of N, showed a V-type line-shape. Our analysis suggests that these magnetic response behaviors depend on the combined effects of intersystem crossing of polaron pairs, reverse intersystem crossing of charge transfer excitons, and triplet-charge interactions under an external field B . This work provides insight into spin-pair dynamic mechanisms occurring within QW-TADF devices and suggests potential applications for a single OLED with integrated magnetic, optical, and electric properties.